Fabrication of a label-free DNA/graphene based electrochemical DNA hybridisation sensor for product authentication and tracing - Hlongwane, Gloria Ntombenhle (My University, 2017)
Poor understanding of the interactions at graphene/DNA interfaces has brought tremendous limitations to the development of label-free DNA-graphene based electrochemical/electrical biosensors. The aim of this study was to develop a label-free DNA/graphene-based electrochemical DNA hybridisation sensor, evaluate and benchmark its output electronic signal as a function of the effect of DNA on graphene’s electronic properties. In addition, the study sought to understand the effect of graphene on the nature of DNA. Herein, results of the investigation of the effects of DNA self-immobilisation and subsequent DNA hybridisation on the electronic structure of CVD-grown graphene using a combination of Raman spectroscopy and conductance measurements are presented. A novel UV-Vis spectroscopy dependent measurement technique for the label-free study of the interaction between DNA-graphene interfaces during DNA hybridisation on graphene is reported. Also presented in this work, is a new method of representing electronic events and DNA conformational changes during DNA detection on graphene from current voltage measurements. Non-covalent assembly was used to immobilise single-stranded (ssDNA) probes on CVD-grown graphene. On CVD-grown graphene, Raman peak frequency shifts, intensities and widths of the G and 2D bands after adsorption of the ssDNA probe and its hybridisation with complementary and mismatched ssDNA strands were analysed. The effect of graphene on the structural and conformational changes of DNA upon hybridisation of the ssDNA on the graphene surface both before and after hybridisation with complementary and triple-base mismatch DNA targets were investigated by monitoring UV-Vis absorption peaks at the 200 nm to 300 nm range. The findings were further confirmed through XRD analysis. Using Riemann approximation method, the rate at which the energy is transformed (power) was computed from the area under current-voltage curves.
A thesis submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy,to the Faculty of Engineering and Built Environment, University of the Witwatersrand. Johannesburg, August 2017
Keywords: DNA--Analysis; Genomics; Polymerase chain reaction